Presence of val30Met and val122ile mutations in a patient with hereditary amyloidosis - Silva-Batista, Jemima A. da; Marques Jr, Wilson [UNESP]; Oliveira, Mayala Thayrine de J. S.; Lins, Lucas Vergne C.; Galvao, Adilson Junior P.; Miguel, Diego Santana Chaves G.; Machado-Costa, Marcela Camara (Nature Publishing Group, 2020)
Amyloidosis, caused by a mutation in the transthyretin (TTR) gene, is the most common hereditary type disease. More than 120 mutations have been described, with extensive phenotypic heterogeneity. Val30Met (p.Val50Met) is the most frequent mutation, and patients exhibit polyneuropathy, possibly including cardiac, renal, gastrointestinal, and/or ocular involvement. Val122Ile (p.Val142Ile) is the mutation associated with cardiomyopathy, and few cases have been reported in Brazil. Most individuals are heterozygous for one pathogenic mutation. Herein, we report a compound heterozygote with two pathogenic mutations (Val30Met/ Val122Ile), and a family history of a deceased brother with amyloidosis, who also carried the same TTR gene mutations. The patient presented with neuropathic, cardiac, and renal impairment and a faster disease progression. Cases of the double mutation have been linked to changes in disease presentation. The concomitance of two pathogenic mutations may have contributed to more exuberant manifestations and faster disease progression.